2020
DOI: 10.1007/jhep02(2020)138
|View full text |Cite
|
Sign up to set email alerts
|

Colliders and conformal interfaces

Abstract: We set up a scattering experiment of matter against an impurity which separates two generic one-dimensional critical quantum systems. We compute the flux of reflected and transmitted energy, thus defining a precise measure of the transparency of the interface between the related two-dimensional conformal field theories. If the largest symmetry algebra is Virasoro, we find that the reflection and transmission coefficients are independent of the details of the initial state, and are fixed in terms of the central… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…It may be useful to note that the interface brane tension in holographic models has also been related [30] to the transmission coefficient [31,32], a quantitative measure the extent to which excitations can pass from one CFT to another across a particular interface.…”
Section: )mentioning
confidence: 99%
“…It may be useful to note that the interface brane tension in holographic models has also been related [30] to the transmission coefficient [31,32], a quantitative measure the extent to which excitations can pass from one CFT to another across a particular interface.…”
Section: )mentioning
confidence: 99%
“…Let us pause here to take stock of the situation. We found that (i) the dual of an isolated interface must correspond to a brane that enters the ergoregion, and (ii) that the brane equations determine in this case the flow of heat in accordance with the CFT result of [24,25] and the transmission coefficients found in [10]. 14 To complete the story, we must make sure that once inside the ergoregion the brane does not come out again.…”
Section: Jhep11(2021)095mentioning
confidence: 78%
“…As noticed in [25], reflection positivity of the Euclidean theory gives a weaker bound [40] than this Lorentzian bound. Note also that in the asymmetric case (c 2 strictly bigger than c 1 ) part of the energy incident from side 2 is necessarily reflected.…”
Section: Jhep11(2021)095mentioning
confidence: 90%
See 2 more Smart Citations